ANSIBLE: Virtual Reality for Behavioral Health. (2016) - Wu, Peggy; Morie, Jacquelyn; Wall, Pete; Ott, Tammy; Binsted, Kim
Abstract: We describe a virtual reality telecommunications ecosystem developed under funding from NASA entitled ANSIBLE: A Network of Social Interactions for Bilateral Life Enhancement. ANSIBLE is a communication support toolset which enables multi-faceted human-human and human-virtual agent interactions designed to accommodate technical and environmental limitations of long duration space flight. The primary objectives are to address communication limitations and provide telehealth options to combat behavioral health threats in future long duration exploration class missions. The system is current being evaluated in a human subject study that takes place at the Hawaii Space Exploration Analog and Simulation (HI-SEAS) facilities in Waimea, HI. There, an international mixed gender group of scientists are undergoing adjustments in physiology and lifestyle that are analogous to some of the challenges in a confined environment over twelve month isolation mission under Mars-exploration conditions (e.g. with communication latencies and blackouts, in close quarters, under restricted water and energy use). Preliminary analysis show that the ANSIBLE treatment group scored better perceived social closeness and perceived relationship satisfaction in self-report surveys compared to a control group who participated in a prior eight month isolation mission in the same facility and used only conventional asynchronous communication methods (i.e. email, voice and video recordings). In the real world, verbal interactions go hand-in-hand with interactions with tangible things. Virtual items can be called upon to serve as powerful and meaningful aides for communications. We posit that the observed increase in social connectedness is due to the affordances of VR, where situational contexts that are often not communicated in traditional telecommunications are made explicit in the virtual world.